Academic staff attitudes and barriers to integrating sustainability in the curriculum at Spanish universities (Actitudes del profesorado y barreras a la sostenibilización curricular en la universidad española). Issue 2 (3rd April 2021) - Olaskoaga-Larrauri, Jon; Guerenabarrena-Cortazar, Leire; Cilleruelo-Carrasco, Ernesto
ABSTRACT: The literature on integrating sustainability in higher education curricula has identified a series of circumstances that can hinder or slow down the transition towards education for sustainable development. This article assesses the influence of two of these circumstances in Spanish universities: teachers' insufficient support for the principles and objectives of sustainable development and their reluctance to consider conveying values as part of their teaching duties. The article collects evidence from the opinions of instructors obtained via a survey, and it concludes that neither of the two circumstances can explain the slowness with which the principles of education for sustainable development are permeating university curricula.